Cultural adaptation and validity of the memorial symptom assessment scale in adults with cancer in Colombia - Gloria Mabel Carrillo; Elizabeth Vargas Rosero; Oscar Yesid Franco; July Liliana Forero; Alejandra Moreno; Melisa Castellanos (Tehran University of Medical Sciences, 2022)
Background & Aim: The Memorial Symptom Assessment Scale measures the presence, frequency, severity, and distress of symptoms. The scale is available in Spanish, but it has not been validated in Colombia. This study aims to translate, validate, and culturally adapt the Memorial Symptom Assessment Scale for adults with cancer in Colombia. Methods & Materials: Adults with cancer undergoing chemotherapy in an oncological outpatient center in Bogota, Colombia, were invited to participate in the study. Patients in end-of-life care or with cognitive deficits were excluded. Psychometric research was carried out and included: 1) Translation and cultural adaptation of the scale from English, 2) Construct validity and reliability with a convenience sample of 249 cancer patients. A factorial analysis of principal components was carried out with the Varimax rotation method in IBM SPSS v26.0. The reliability of the scale was estimated using Cronbach's Alpha; subsequently, factor analysis was carried out using structural equations in MPlus. Results: The scale was adapted to the Colombian context. Two factors (physical and psychological) of the scale structure were produced by the factorial analysis that contributes 47.9% of the accumulated variance. The alpha coefficient of Cronbach ranged between 0.75 and 0.79. The final model goodness of fit was also adequate [X2 (128)=184.47, p = 0.008, CFI = 0.94, RMSEA: 0.04 [0.03, 0.06], SRMR: 0.06, TLI= 0.92]. Conclusion: The Memorial Symptom Assessment Scale has adequate validity and reliability to measure the prevalence, frequency, stress, and severity of symptoms in adults with cancer in Colombia.